ANALISIS FATWA DSN MUI NO: 04/DSN-MUI/IV/2000 TERHADAP PENERAPAN AKAD MURABAHAH PADA PRODUK CICIL EMAS PADA BANK SYARIAH MANDIRI KCP. CIKUPA TANGERANG-BANTEN - Suardi, Didi (Islamic Economics Program, Faculty of Islamic Economics and Business, 2021)
This study concludes that the financing mechanism for the BSM Installment Gold product at BSM KCP. Cikupa consists of several stages starting from the requirements for submission, valuation of collateral, termination of financing, implementation of contracts and financing of financing. In the financing process for the financing of the Gold Installment Product, BSM KCP. Cikupa is in accordance with the guidelines of the DSN-MUI fatwa No: 04/DSN-MUI/IV/2000 concerning Murabahah, but there are some that are not in accordance with the first provisions of the ninth point, where at the time of the contract agreement process, gold was still in the ordering stage to PT. Antam and not owned by the bank. The type of research used is field research (field research). The data sources of this research consist of primary and secondary sources obtained through interviews, documentation, and other scientific literature. The data that has been collected, then analyzed using descriptive analysis method.